Impact of Smoking on Halitosis and Oral Bacterial Infections - Doaa Raad Alghaffari; Mays Wael Sulaiman Al Alousi; Raya Alani; Dina Ahmed Mahdi (Dentistry 3000)
Objective: The present study sought to investigate the frequency of halitosis in a sample of smokers and non-smokers and the association of smoking and perceived oral bacterial infections. Material and Methods: A questionnaire was administered to 301 respondents. The structured questionnaire included demographics, oral hygiene behaviors, medical and dental history, lifestyle behaviors, awareness of halitosis and its social consequences in others. Statistical analyses were performed with chi-square tests to identify any associations of halitosis and possible risk factors. Results: Among respondents, 22.9% self-reported using tobacco products while 63.4% self-reported experiencing halitosis sometimes or frequently. Smoking, periodontal disease, dental caries, poor clinical hygiene (not brushing, not flossing or using mouthwash) and some systemic diseases were related to self-reporting halitosis (P < 0.01). Only 9.6% of respondents accessed treatment. Most respondents (86%) realized their halitosis themselves rather than it being diagnosed professionally. Conclusion: This study provides insight into the relationship between smoking and self-reported halitosis and the need for greater awareness and tailored public health initiatives.